2016
DOI: 10.1002/psp.2004
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well-being of Ghanaian Children in Transnational Families

Abstract: This study is one of the first large‐scale analyses on child psychological well‐being in the context of parental migration when children remain in an African country. As such, it contributes to the literature by investigating some of the insights gained from in‐depth transnational family studies, and it also provides evidence from Africa where normative contexts around family life differ from Latin America, Southeast Asia, and East Asia where most studies have been conducted to date. A survey was conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 38 publications
4
58
0
Order By: Relevance
“…In Malawi, Carling and Tønnessen (2013) found that children whose father is deceased or whose parents are divorced are worse off in terms of nutrition, fever and diarrhoea, when compared to children whose fathers are either present or migrants. In Ghana, Mazzucato and Cebotari (2016) emphasised similar costs of separation when measuring psychological health of children whose parents migrated and were divorced. On the contrary, research based on Multiple Indicator Cluster Surveys (MICS) and Demographic and Health Surveys (DHS) found no difference in nutritional outcomes among orphan and non-orphan children in 23 African countries, including Ghana and Nigeria (Rivers et al, 2008).…”
Section: Transnational Families and Child Healthmentioning
confidence: 99%
“…In Malawi, Carling and Tønnessen (2013) found that children whose father is deceased or whose parents are divorced are worse off in terms of nutrition, fever and diarrhoea, when compared to children whose fathers are either present or migrants. In Ghana, Mazzucato and Cebotari (2016) emphasised similar costs of separation when measuring psychological health of children whose parents migrated and were divorced. On the contrary, research based on Multiple Indicator Cluster Surveys (MICS) and Demographic and Health Surveys (DHS) found no difference in nutritional outcomes among orphan and non-orphan children in 23 African countries, including Ghana and Nigeria (Rivers et al, 2008).…”
Section: Transnational Families and Child Healthmentioning
confidence: 99%
“…Transnational familyhood as a social formation sustained through cultivating multifaceted social and emotional ties across borders is characterised by the frequent physical comings and goings of key family members (Basch, Glick Schiller, & Blanc‐Szanton, ; Bryceson & Vuorela, ; Sørensen & Vammen, ). Although much attention has been paid to the formation, maintenance, and practices of transnational families, the research focus has been distributed unevenly in favour of adults'—both migrant and left‐behind members'—perspectives thus far, with less consideration of children's experiences (exceptions include Dreby, ; Graham, Jordan, Yeoh, Lam, & Asis, ; Mazzucato & Cebotari, ). To address this gap, recent literature has begun encouraging a more “children‐inclusive approach” to studying transnational families.…”
Section: Introductionmentioning
confidence: 99%
“…Families with histories associated with negative outcomes for children, including divorce or separation of parents, migration of mother, poor school record, or child behavioural problems, and families with few supportive family members were ranked lower (Hoang, Lam, Yeoh, & Graham, ; cf. Mazzucato & Cebotari, ). We produced a continuum of family provisioning for children.…”
Section: Methodologiesmentioning
confidence: 99%
“…Often referred to in academic literature as “left‐behind” children, we advocate the term stay‐behind to avoid implying that parents have neglected or abandoned their children, and to emphasise the relatively sedentary circumstances of the children compared with their parents' mobility. The impacts of parental migration on stay‐behind children have received growing attention internationally (e.g., Coe, ; Dreby, ; Leinaweaver, ; Mazzucato & Cebotari, ), including in Asia and the Pacific region (e.g., Alipio, Lu, & Yeoh, ; Choi, Yeoh, & Lam, ; Graham & Jordan, ; Graham, Jordan, Yeoh, Lam, & Asis, ; Murphy, Zhou, & Tao, ; Toyota, Yeoh, & Nguyen, ). However, largely neglected by investigators are the strategic actions of parents around registering stay‐behind children in order to gain access to services and resources such as education, health care, or food subsidies.…”
Section: Introductionmentioning
confidence: 99%